Per-Vaginal Delivery of Dicephalus Fetal Monster in a Buffalo (Bubalus bubalis) - Verma, Sanjeev Kumar; Kumar, Rajesh; Saurabh,; Singh, Kunwar Dhananjay; Kumar, Abhishek (The Indian Journal of Animal Reproduction, 2025)
This case report documents a rare occurrence of a dicephalus fetus in a buffalo and its per-vaginal delivery through the  obstetrical manoeuvre. The buffalo was recovered uneventfully.
Keywords: Buffalo; Dicephalus Monster; Dystocia; Fetus; Management